2004
DOI: 10.1111/j.1365-4632.2004.02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisturizing effects of topical nicotinamide on atopic dry skin

Abstract: Nicotinamide cream is a more effective moisturizer than white petrolatum on atopic dry skin, and may be used as a treatment adjunct in atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…Niacinamide is involved in the biosynthesis of ceramides in keratinocytes by activating the mRNA expression of serine palmitoyltransferase, the key enzyme for the sphingolipid synthesis [30]. As a result the increased rate of ceramide synthesis again influences the barrier effect of the stratum corneum [31,32]. Niacinamide is also a potent inhibitor of cAMP-phosphodiesterase, stabilises the mast cells and therefore reduces the release of histamine [33,34,35,36,37,38,39].…”
Section: Biological Effects With Dermatological Relevancementioning
confidence: 99%
“…Niacinamide is involved in the biosynthesis of ceramides in keratinocytes by activating the mRNA expression of serine palmitoyltransferase, the key enzyme for the sphingolipid synthesis [30]. As a result the increased rate of ceramide synthesis again influences the barrier effect of the stratum corneum [31,32]. Niacinamide is also a potent inhibitor of cAMP-phosphodiesterase, stabilises the mast cells and therefore reduces the release of histamine [33,34,35,36,37,38,39].…”
Section: Biological Effects With Dermatological Relevancementioning
confidence: 99%
“…The existing preclinical data show that NIC has the potential for topical application in cosmetic or pharmaceutical industry because of its barrier restoration, anti-inflammatory, and depigmenting effects. 41,42 Moreover, NIC has a therapeutic potential as an inhibitor of proinflammatory cytokines in inflammatory disease. 43 Activation of NF-κB is a very important factor in both lesional and nonlesional skin from patients with psoriasis.…”
mentioning
confidence: 99%
“…Moreover, C. olitorius contains significant amounts of vitamin E and vitamin B 3 [2]. It has previously been reported that vitamin E improved the symptoms of AD by decreasing the concentrations of inflammatory factors [22], and that nicotinamide, which is the amide of vitamin B 3 , promoted a decrease in TEWL on atopic dry skin [23]. These compounds may play a role in the observed efficacy of COEW on ADlike inflammation.…”
Section: Skin Hydrating Effects Of Corchorus Olitorius Extract In a Mmentioning
confidence: 97%